A peptide of the N-terminus of GRK5 attenuates pressure-overload hypertrophy and heart failure - Coleman, Ryan C. (Sci Signal, 2021)
Aberrant changes in gene expression underlie the pathogenesis and progression of pressure-overload heart failure, leading to maladaptive cardiac hypertrophy, ventricular remodeling, and contractile dysfunction. Signaling through the G protein Gq triggers maladaptation and heart failure, in part through the activation of G protein-coupled receptor kinase-5 (GRK5). Hypertrophic stimuli induce the accumulation of GRK5 in the nuclei of cardiomyocytes, where it regulates pathological gene expression through multiple transcription factors including NFAT. The nuclear targeting of GRK5 is mediated by an amino-terminal (NT) domain that binds to calmodulin (CaM). Here, we sought to prevent GRK5-mediated pathology in pressure-overload maladaptation and heart failure by expressing in cardiomyocytes a peptide encoding the GRK5 NT (GRK5nt) that encompasses the CaM binding domain. In cultured cardiomyocytes, GRK5nt expression abrogated Gq-coupled receptor-mediated hypertrophy, including attenuation of pathological gene expression and the transcriptional activity of NFAT and NF-κB. We confirmed that GRK5nt bound to and blocked Ca(2+)-CaM from associating with endogenous GRK5, thereby preventing GRK5 nuclear accumulation after pressure overload. We generated mice that expressed GRKnt in a cardiac-specific fashion (TgGRK5nt mice), which exhibited reduced cardiac hypertrophy, ventricular dysfunction, pulmonary congestion, and cardiac fibrosis after chronic transverse aortic constriction. Together, our data support a role for GRK5nt as an inhibitor of pathological GRK5 signaling that prevents heart failure.